Elemental analysis of some clay sampels by a modified x-ray fluorescence technique / Ahmad Saat - Saat, Ahmad (Universiti Teknologi MARA, Pahang, 1991)
Elemental analysis of several Malaysian clays have been carried out using x-ray fluorescence technique with a modified sample preparation method. To minimize concentration and matrix effect, the dilution technique is employed in the preparation of samples for analysis. The results obtained show reasonable accuracy and repeatability.